2005
DOI: 10.1038/sj.gt.3302672
|View full text |Cite
|
Sign up to set email alerts
|

Selective proapoptotic activity of a secreted recombinant antibody/AIF fusion protein in carcinomas overexpressing HER2

Abstract: Apoptosis-inducing factor (AIF) represents a caspase-independent apoptotic pathway in the cell, and a mitochondrial localization sequence-truncated AIF (AIFD1-120) can be relocated from the cytoplasm to the nucleus and exhibit a constitutive proapoptotic activity. Here, we generated a chimeric immuno-AIF protein, which comprised an HER2 antibody, a Pseudomonas exotoxin translocation domain and AIFD1-120. Human Jurkat cells transfected with the immuno-AIF gene could express and secrete the chimeric protein, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Recent reports have observed that AIF is downregulated in many tumor types (Delettre et al, 2006), and depletion of the AIF protein in malignant skin, colon, lung, and breast cells contributes to chemoresistance, supporting AIF pro-cell-death functions in the context of cancer (Huerta et al, 2007). A HER2 antibody-AIF protein chimeric molecule significantly prolonged survival of mice with tumors that over-express HER2 (Yu et al, 2006). Indeed, nuclear BNIP3 repressed AIF expression to a greater extent than other apoptotic proteins as determined by a cDNA microarray analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have observed that AIF is downregulated in many tumor types (Delettre et al, 2006), and depletion of the AIF protein in malignant skin, colon, lung, and breast cells contributes to chemoresistance, supporting AIF pro-cell-death functions in the context of cancer (Huerta et al, 2007). A HER2 antibody-AIF protein chimeric molecule significantly prolonged survival of mice with tumors that over-express HER2 (Yu et al, 2006). Indeed, nuclear BNIP3 repressed AIF expression to a greater extent than other apoptotic proteins as determined by a cDNA microarray analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the transduced lymphocytes had potent and selective cytotoxicity to tumors both in culture and nude mouse models. 13,14,[20][21][22] In this study, we modified this cell-based therapy strategy by delivering the therapeutic molecules into muscle cells neighboring the tumor tissue. In in vivo experiments, we found that ImmunoGrB (PEA253-358aa), ImmunoGrB (PEA275-358aa) and ImmunoGrB (PEA275-280aa) could all inhibit tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have developed a cell-based therapy by genetically modifying lymphocytes to produce and secrete a targeted PEA toxin against HER2-positive tumor cells. 13,14,[20][21][22] In such a strategy, we combined the specificity of antibodies, the potent cytotoxicity of apoptotic executioners, and the effector cell properties of lymphocytes such as homing and tissue penetration. A signal sequence was introduced into the constructs to ensure that the immunotoxins are secreted by genetically modified cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a chimeric protein containing an ErbB-2-specific antibody in the C-terminus and the cytotoxic moiety of AIF in the N-terminus has been shown to direct AIF to ErbB-2-expressing cancer cells, causing their demise (Yu et al, 2006). This strategy of tumor killing could be used for anticancer therapy in vivo, as demonstrated in mice xenotransplanted with human ErbB-2-overexpressing cancer cells when the chimeric protein was produced by Jurkat T-lymphoma cells that were coinoculated (Yu et al, 2006).…”
Section: Chemotherapy and Mitochondriamentioning
confidence: 99%